PELAKSANAAN PRAKTIK SHALAT DHUHA UNTUK MENGEMBANGKAN KARAKTER RELIGIUS ANAK DI TK MUJAHIDIN PONTIANAK - Pengestika, Gita; Marmawi, Marmawi; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to knowing how to implementation of dhuha prayer for develop religious character in children aged 5-6 years old in TK Mujahidin 1 Pontianak Selatan. The research method used is descriptive with qualitative research. The data source of this research is 1 teacher and 16 children from group B6th in TK Mujahidin 1 Pontianak Selatan. Technique this research is observation with observation sheet, interview technique directly with the interview form tool and with documentary. Analysis of the data of this research is data collection, data reduction, presentation and conclusion the documentation tool. Based on the results of research that has been done and through the results obtained from data analysis, generally conclusions can be drawn namely at the implementation of the practice of dhuha prayer in the presence of dhuha prayer ie reading intention to pray dhuha is done with guidance by the class teacher with the method habituation by repeating the intention of daily prayers together. Then, following the prayer movement is carried out with the guidance of the teacher who is the imam, The teacher uses the exemplary method to set an example for children by participating and the dhuha prayer in congregation. Next, recite the prayer after the dhuha prayer is led by teachers who are followed by students together after the dhuha prayer with daily habituation methods that are carried out together.Key words: Religious Character, Dhuha Prayer